2017
DOI: 10.3892/ol.2017.7019
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of 125I seed implantation in the treatment of non‑small cell lung cancer during R2 resection

Abstract: The aim of the present study was to investigate the effectiveness of 125I particle implantation during R2resection for non-small cell lung cancer (NSCLC). Data from 23 patients with NSCLC and macroscopic residual diseasefollowing surgery (R2 resection) between March 2010 and May 2014 were retrospectively analyzed. Among these patients, 12 patients [4 with T-residual disease (incomplete resection of primary tumor but complete dissection of regional lymph node), 8 with N-residual disease (complete resection of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Another study confirmed that 125I seed implantation can effectively improve the disease control rate relative to conventional radiotherapy and chemotherapy in lung cancer patients [7]. 125I seed implantation is considered as an effective therapeutic option for patients with advanced lung cancer who have failed first-line chemotherapy [8,9]. In view of this, the results showed that the disease remission rate was 41.18% with 125I seed implantation.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Another study confirmed that 125I seed implantation can effectively improve the disease control rate relative to conventional radiotherapy and chemotherapy in lung cancer patients [7]. 125I seed implantation is considered as an effective therapeutic option for patients with advanced lung cancer who have failed first-line chemotherapy [8,9]. In view of this, the results showed that the disease remission rate was 41.18% with 125I seed implantation.…”
Section: Discussionmentioning
confidence: 84%
“…Step-bystep radiotherapy and chemotherapy have killing effects on T lymphocytes and normal tissue cells when killing cancer cells [17]. 125I seed implantation under the guidance of TPS system can advance accurate and precise radiation range; in addition to ensure the effective radiation dose in cancer target area, the damage to surrounding organs and tissues is small, which is beneficial to improve immune function of the body [9]. Besides that, BACE, as a local interventional chemotherapy, injects chemotherapeutic drugs into the lesion through a microcatheter and embolizes the target vessel with gelatin sponge; in addition to achieve antitumor effect, BACE has little influence on T lymphocytes and normal tissue cells and can effectively regulate immunity while inhibiting tumor growth [18].…”
Section: Discussionmentioning
confidence: 99%
“…These lymph nodes can contribute to metastatic spread, thereby affecting the long-term survival of patients [4,5,[26][27][28][29][30]. 125 I brachytherapy, with a higher local concentration of radiotherapy, is particularly well suited for the treatment of retroperitoneal metastasis [31][32][33][34]. Yao [19] et al reported 17 patients with 19 retroperitoneal metastatic lymph nodes who received 125 I brachytherapy with an overall effective rate of 100%.…”
Section: Discussionmentioning
confidence: 99%
“…For stage IIIA and IIIB patients, the 5-year survival rates were 19.63% and 10.0%, with median survival time of 26.67 and 24.59 months, respectively. Huang [ 21 ] has reported 32 patients of stage IIIB NSCLC treated with radical resection and implantation of radioactive 125 I seeds; their 1- and 3-year survival rates were 63.8%, and 31.9%, respectively. At present, many studies have reported the significant short-term therapeutic efficacy of radioactive seed implantation for lung cancer, but only a few reports have discussed its long-term therapeutic efficacy; these studies include only a small number of cases.…”
Section: Discussionmentioning
confidence: 99%